Pengaruh Lingkungan Kerja Dan Job Description Terhadap Prestasi Kerja Pegawai Pada Sekretariat DPRD Provinsi Sumatera Selatan - Riskiyah, Miftakur; Damayanti, Reina; Kurbani, Adie (Jurnal Ilmiah Wahana Pendidikan, 2024)
Abstract This study aims to test the hypothesis of the influence of work environment and job description on employee job performance at the Secretariat of the Regional People's Representative Council (DPRD) of South Sumatra Province. The sampling technique used in this study was a saturated sample technique with a total of 91 civil servant respondents. The research data were analyzed using Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Coefficient of Determination Analysis, as well as t-test and F-test. The results of the hypothesis test indicate that there is a partial influence of the Work Environment (X1) on Employee Job Performance, with a significance level of 0.000 < 0.05. In addition, the Job Description variable (X2) also has a significant influence on Employee Job Performance, with a significance level of 0.000 < 0.05. Therefore, it can be concluded that both factors, namely Work Environment and Job Description, have a significant influence on Employee Job Performance. Furthermore, the results of the simultaneous F-test show that there is a significant influence of Work Environment and Job Description on Employee Job Performance, with a significance level of 0.005 < 0.05. Keywords: Work Environment, Job Description, Job Performance